Diagnostic evaluation of heel prick newborn screening of thyroid stimulating hormone on dissociation-enhanced lanthanide fluorescence immunoassay with the establishment of reference value in Pakistani neonates - Ayesha Raza; Ambreen Barkat; Safia Fatima; Fizza Faizan Farooqui; Naureen Chaudhri; Shahzad Haider (Journal of the Pakistan Medical Association, 2020)
Objective: To develop and validate a method on Dissociation Enhanced Lanthanide Fluorescence Immunoassay for neonatal heel prick blood human thyroid stimulating hormone and the establishment of its reference value in the local population. Methods: The multi-centre cross-sectional validation study was conducted from September 2016 to September 2018 at Zahra Beau Naqvi Foundation Welfare Trust laboratory, Islamabad, Pakistan, and comprised samples related to newborns aged 1 month or less taken from neonatal units of 39 hospitals based in Punjab, Khyber Pakhtunkhuwa, Gilgit-Baltistan and Azad Jammu and Kashmir. Samples were collected after 24 hours of birth using the heel prick test. The samples were dried and sent to the laboratory for assessment where Dissociation Enhanced Lanthanide Fluorescent Immunoassay was used to estimate thyroid stimulating hormone levels. Data recorded included age, gender, and birth detail, like gestational age, mode of delivery etc. Data was analysed using SPSS 21. Method validation and reference value were manually calculated. Results: Of the 14,147 samples received, 8,207(58%) related to boys and 5,940(42%) to girls. Most samples 4903(34.6%) came from Peshawar. The overall mean age of the newborns was 5.6±4.8 days. Thyroid stimulating hormone data was divided into three groups; positive with median value 27.8±36.6 uIU/ml, negative with median 1.42±1.60 uIU/ml, and borderline with median 11.4±4.12uIU/ml. Prevalence of congenital hypothyroidism in high-risk population in the positive group was 39(0.3%), negative 14,012(99.0%) and borderline 96(0.7%). Continuous...